Substantial gains and little downside from farming of Totoaba macdonaldi - Julia M. Lawson; Simon Jean; Andrew Steinkruger; Miguel Castellanos-Rico; Garrett M. Goto; Miguel Á. Cisneros-Mata; Erendira Aceves-Bueno; Matthew M. Warham; Adam M. Sachs; Steven D. Gaines (npj Ocean Sustainability)
Abstract Illegal wildlife trade threatens species globally. Conservation farming introduces farmed substitutes to reduce poaching. Predicting if farming will succeed necessitates understanding how supply and demand interact and how markets respond. We focus on illegal trade for totoaba (Totoaba macdonaldi), dominated by a Mexican cartel, which has continued unabated despite long-standing prohibitions. We investigate if farmed totoaba can successfully compete with poaching and support a healthy wild totoaba population. We simulate an illegal supply chain describing the current trade: poachers sell to traders who sell to end-markets. If traders reduce the quantity supplied in response to farming, poaching could decrease by 28%, but if traders select a price that undercuts farming, poaching may increase by 6%. Under both responses, a stable wild population is maintained. Our results are sensitive to costs, demand, product substitutability, market structure, and combinations thereof, and we discuss how to quantitatively evaluate and mitigate for these issues.